2021
DOI: 10.1111/pcmr.13023
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerated melanoma: Systems biology evidence of inflammatory imbalance towards pro‐tumourigenicity

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…A melanoma tumor with a speed of growth exceeding that of the normal keratinocytes may lead to epidermal attenuation and eventual ulceration. Indeed, pathways associated with cellular proliferation have been shown through genomic and transcriptomic analyses to be upregulated in ulcerated tumors compared with nonulcerated tumors . Hypoxia may also be a contributing factor; rapidly proliferating malignant cells may compress the small vessels supplying the epidermis and deplete the microenvironment of oxygen with their own high metabolic demands .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A melanoma tumor with a speed of growth exceeding that of the normal keratinocytes may lead to epidermal attenuation and eventual ulceration. Indeed, pathways associated with cellular proliferation have been shown through genomic and transcriptomic analyses to be upregulated in ulcerated tumors compared with nonulcerated tumors . Hypoxia may also be a contributing factor; rapidly proliferating malignant cells may compress the small vessels supplying the epidermis and deplete the microenvironment of oxygen with their own high metabolic demands .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, pathways associated with cellular proliferation have been shown through genomic and transcriptomic analyses to be upregulated in ulcerated tumors compared with nonulcerated tumors. 19 Hypoxia may also be a contributing factor; rapidly proliferating malignant cells may compress the small vessels supplying the epidermis and deplete the microenvironment of oxygen with their own high metabolic demands. 20 These deficits may produce keratinocyte ischemia, loss of epidermal integrity, and ultimately ulceration.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ulceration denotes a highly proliferative lesion, often associated with a high mitotic rate, but not all thick melanomas with important mitotic activity are ulcerated, which suggests the influence of other additional factors in the development of ulceration [ 36 , 37 , 38 ]. Because of the aggressive biological behavior associated with ulceration, a hypothesis was issued stating that this develops as a consequence of some intrinsic biological factors of the tumor, supporting dissemination and loss of epidermis integrity [ 36 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“… 10 The association between low vitamin D and ulceration has been hypothesized to be the result of altered Wnt/β-catenin signaling. 22 In 2017, von Schuckmann et al showed that patients who regularly used statins, aspirin or NSAIDs were less likely to be diagnosed with an ulcerated melanoma when incidence was adjusted for age, sex, thickness and mitotic rate (OR 0.68, 95% CI 0.46–1.00). 23 While early epidemiologic studies suggested that statins may prevent melanoma development, more recent studies do not support this finding.…”
Section: Introductionmentioning
confidence: 99%